Pengaruh Kinerja Administratif dan Kualitas Pelayanan Pendidikan terhadap Kepuasan Peserta Didik - Arrifqi Waliyuddin; Siti Khoirun Nisak (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Administrative performance as part of the school’s managerial function plays an important role in shaping students’ perceptions and levels of satisfaction. In addition, the quality of educational services has been proven to be a dominant variable that significantly affects student satisfaction; therefore, the quality of educational services is the main determinant of satisfaction among users of educational services. This study aims to determine whether administrative performance and the quality of educational services have a positive and significant effect on student satisfaction The research method used is an associative quantitative approach with a cause-and-effect relationship. The research population consisted of 243 eleventh-grade students of SMK Unggulan NU Mojoagung Jombang, and the sample was determined using the Krejcie and Morgan table, resulting in 152 respondents. Data collection techniques included questionnaires and documentation, using instruments that were established and tested through validity and reliability tests. Data analysis employed multiple linear regression to test the hypotheses both partially and simultaneously using SPSS 20.0 for Windows. The results of the study indicate that:(1) Administrative performance has a positive and significant effect on student satisfaction, as shown by a significance value of 0.000 < 0.05 and a t-value of 16.667 > t-table of 1.655. Thus, H0 is rejected and H1 is accepted, with a contribution effect of 0.097 or 9.7%. (2) The quality of educational services also has a positive and significant effect on student satisfaction, with a significance value of 0.000 < 0.05 and a t-value of 21.843 > t-table of 1.655, so H0 is rejected and H1 is accepted, with an effect size of 0.681 or 68%. (3) Simultaneously, administrative performance and the quality of educational services have a positive and significant effect on student satisfaction, as evidenced by an F-value of 244.637 > F-table of 3.06 with α = 0.000 < 0.05.